Katalog polnaravnih travišč Slovenije - Škornik, Sonja; Paušič, Igor; Bakan, Branko; Mitja Kaligarič, Mitja Kaligarič (University of Maribor Press, 2023)
The Catalogue of seminatural Grasslands of Slovenia. The monograph deals with semi-natural grasslands, which in Slovenia and in Europe represent a species-rich, strongly declining vegetation and at the same time are a relic of the traditional agricultural landscape. In the introduction, the historical development and importance of semi-natural grasslands are presented. Due to the drastic decline of their areas, they have become one of the most threatened habitats in Europe and most of them are listed in Annex I of the Habitats Directive. A new measure of the agri-environmental and climate payments "Colorful Meadow" was also presented, which we developed as part of a targeted research project. Important additional information is provided by the various established classifications of habitat types (Syntaxonomic, Physis, EUNIS, FFH typologies). The central part of the book is dedicated to a detailed presentation of each grassland type: Indicator plant species, ecology, distribution, management and conservation. The title of the work is a "Catalogue" because it is systematic, transparent and well illustrated. The book is intended for experts and researchers in biology, ecology, nature conservation and agriculture, students of biological and ecological studies, as well as the general public or readers who are interested in nature and the conservation of biotic diversity.